C3G overexpression promotes the survival of rat‐derived H9C2 cardiomyocytes by p‐ERK1/2. (5th June 2013) - Zhang, Xu; Li, Gang; Zhang, Lei; Yang, Dongyan; Zhang, Zhisheng; Yan, An; Linghu, Hua
Abstract: Integrin β1 subunit and its downstream molecules, such as integrin‐linked kinase and focal adhesion kinase, are imperative for promotion of cell proliferation, survival and anti‐apoptosis in cardiomyocytes by activation of their downstream pro‐survival signalling molecules, such as the phosphorylated extracellular signal‐regulated kinase1/2 (p‐ERK1/2). As a component of the integrin pathway, C3G (Crk‐SH3 domain guanine nucleotide exchange factor) protein may be involved in the promotion of cell proliferation and survival and anti‐apoptosis in the H9C2 cardiomyocytes. Rat‐ derived H9C2 cardiomyocytes were transfected with pCXN2‐flag‐hC3G, a human C3G overexpression eukaryotic recombinant plasmid. Apoptosis, cell proliferation and survival were analysed in the H9C2 cardiomyocytes either treated with hypoxia/reoxygenation (H/R). Human C3G mRNA overexpression significantly elevated C3G protein expression in H9C2 cardiomyocytes whether treated with H/R or not. C3G overexpression promoted proliferation and survival and anti‐apoptosis, and attenuated the proliferative and survival inhibition, and apoptosis induced by H/R by activation of its downstream pro‐survival signalling molecule, p‐ERK1/2. The results suggest that C3G acts as a pro‐survival molecule in H9C2 cardiomyocytes by activation of p‐ERK1/2.